PREDIKSI FINANCIAL DISTRESS MENGGUNAKAN PERTUMBUHAN PENJUALAN DAN CORPORATE GOVERNANCE PADA PERUSAHAAN SEKTOR PERTAMBANGAN - Shintia Ramdani; Indra Wijaya (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
The aim of the research was to examine the accuracy of sales growth and corporate governance in predicting financial distress in the mining sector companies. Corporate governance in this research used indicator size of the board of directors, board of commissioners, independent commisioners, and audit comitte. Financial distress used earning per share (EPS) as a proxy. The population of this research were 43 mining companies listed on the Indonesian Stock Exchange for the period 2012-2016. The sample obtained by purposive sampling method were 11 companies of mining sector. Data analyze used logistic regression by SPSS 24 program. The results of the research indicated that sales growth, board of commissioners, audit committee had no significant effect in predicting financial distress, while the size of the board of directors and independent commissioners had a significant negative effect in predicting financial distress.